How to Write Dissertations & Project Reports - McMillan, Kathleen and Weyers, Jonathan D. B. (Delhi Pearson, 2014)
Students need more help than ever before in selecting their dissertation or project topic and ensuring this major project gets the best marks. This book provides crucial support that will help organise their thinking and get them on the road to success.
Include References and Glossary
Keywords: Report writing -- Dissertations, Academic--Authorship -- Dissertations, Academic